Deiksis Persona, Waktu, Dan Tempat Dalam Cerita Rakyat Subsuku Dayak Uud Danum - Rohrodo, Fransiska Yunita Serwenda; Nadeak, Parlindungan; Syahrani, Agus Syahrani (CV. ITTC INDONESIA, 2024)
This study aims to describe the form of deixis persona, time, and place, describe the meaning of deixis persona, time and place based on the folklore of Dayak Uud Danum sub-tribe in Buntut Purun Village, Ambalau District, Sintang Regency. and produce a form of implementation of Indonesian language learning. The method used in this research is descriptive method with qualitative form. The data sources in this research are folktales entitled (1) Moruan Asuk, (2) Tomakung Koling, (3) Songumang, and (4) Mosihkin obtained from informants who are native speakers of the Dayak Uud Danum language, and the data of this study are in the form of words, phrases, sentences, and paragraphs that show the existence of events or properties of deixis persona, time, and place. Data collection techniques are observation techniques, interview techniques, and recording techniques. This research found 374 uses of persona, time, and place deixis, consisting of 322 uses of persona deixis, 18 uses of time deixis, and 34 uses of place deixis. The form of implementation based on this research is a learning text, namely narrative text (fantasy story).